Sistem Informasi Repository Skripsi pada Jurusan Teknologi Informasi dan Komputer Menggunakan Metode Sequential Search - Azhar, Amri (Jurnal Elektro dan Informatika, 2020)
One aspect of the success of a company is the management of human resources. Power outlets help standardized integrated electricity services that provide convenience, transparency of information, quality assurance and safety protection for electricity users, while consistently maintaining and improving the services produced so that they are always in accordance with predetermined standards. The power outlet assessment can motivate the morale of each power outlet to improve the dedication and performance of a company. With 6 numbers of power outlets registered at PT. PLN up3 Lhokseumawe with various kinds of assessments it will be difficult to determine which outlets deserve an award. For this reason, a decision support system is needed using the Simple Additive Weighting Method to be able to assist in the assessment of power outlets. The Simple Additive Weighting method is to find the weighted sum of the performance ratings for each alternative on all attributes. The aim of this research is to design a best power outlet rating system. The calculation method uses the result of the largest value which will be selected as the best alternative. The criteria used are performance, finance, facilities, service quality, cooperation, and report results. The results of this study indicate that the best power outlet rankings with the highest value of 92.3 and the lowest value of 36.2 and have been proven by manual calculations and the results of system analysis are the same